1964
DOI: 10.1111/j.1537-2995.1964.tb02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Prevention of Experimental Rh Sensitization in Man with an Anti‐Rh Gamma2‐Globulin Antibody Preparation: A Preliminary Report

Abstract: An anti‐Rh gamma2‐globulin antibody preparation has been developed which can be administered intramuscularly and appears to be both safe and effective in the prevention of experimental Rh sensitization. Nine unsensitized Rh‐negative male volunteers were challenged once a month for five successive months with intravenous injections of 2 ml. of Rh‐positive blood. Four of these nine volunteers were passively protected each month with intramuscular injections of 5 ml. of this antibody preparation, administered 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

1967
1967
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(53 citation statements)
references
References 28 publications
0
51
0
2
Order By: Relevance
“…(1961) and Clarke et at. (1963) and in the U.S. A. Freda et al (1964) showed conclusively that Rh-disease could be prevented by passive immunization with high-titre anti-D plasma or anti-D ganmaglobulin.…”
Section: Methodsmentioning
confidence: 99%
“…(1961) and Clarke et at. (1963) and in the U.S. A. Freda et al (1964) showed conclusively that Rh-disease could be prevented by passive immunization with high-titre anti-D plasma or anti-D ganmaglobulin.…”
Section: Methodsmentioning
confidence: 99%
“…Prevention of RhD HDFN became feasible in the late 1960s after pioneering research by Finn Clarks and Freda; there was a dramatic decline in Rh HDFN [19,20]. Since then other Rh and nonRh red cell alloantibodies have become relatively more important and are now responsible for the greater proportion of the HDFN cases.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the use of RhoGAM, 1 in 100 babies were affected with a high risk of intrauterine demise or neonatal hydrops. 55 Ninety-five percent of the cases are now prevented, with an accompanying dramatic decrease in the need for double volume exchange transfusions and the occurrence of kernicterus.…”
Section: S: Contemporary Newborn Medicinementioning
confidence: 99%